A novel anticandidal compound containing sulfur from endophytic Fungus emericella sp - Mittal, S.; Shrivastava, D.; Govil, S.; Kumar, S.; Bisen, P.S.
Background: Endophtes live symbiotically in the tissues of host plants without causing visible harm. These endophytes produce not only the plant bioactive metabolites but also a host of unexplored structurally diverse natural products having biological activity. New niches may be explored for bioprospecting endophytes for the development of novel candidate molecules having industrial applications. Methods: The bioactive compound is isolated from the endophyte Emericella sp. associated with Azadirachta indica A. Juss (Neem), that potentially inhibits or prevents the human pathogenic disease caused by Candida albicans. The molecule was characterized by employing TLC, IR and GCMS. The isolated compound was identified as N-[(2S, 3aR, 6S, 7aS)-6-acetamido-octahydro-1,3-benzothiazol-2-yl]2- (adamantan-1-yl)acetamide having sulfur. Results: In the present study, a new molecule containing sulphur inhibits the growth of Candida specifically. The molecule can serve as a lead molecule for designing new drugs having anticandidal activity. The compound having anticandidal activity belongs to the class of antifungal agent - allylamine, azole and polyene. Conclusion: A new molecule containing sulphur and inhibiting specifically C. albicans is reported in the present study. They are known to promote plant growth and yield, act as biocontrol agents and are known to produce secondary metabolites, such as enzymes, growth hormones, antimicrobial, antifungal, or anticancerous substances.
Keywords: ANTICANDIDAL DRUG; AZADIRACHTA INDICA; CANDIDA ALBICANS; EMERICELLA; ENDOPHYTE